1997
DOI: 10.1159/000203603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha-interferon on Natural Killer Cell Activity and Lymphocyte Subsets in Thalassemia Patients with Chronic Hepatitis C

Abstract: The variation of natural killer (NK) cell activity and lymphocyte subsets 20 h after a single test dose of α-IFN, was studied in 17 thalassemic patients with chronic hepatitis C. All patients had suspended the α-IFN therapy at least 12 months before the study: 10 were considered responders and 7 nonresponders. Also NK cell cytotoxicity after in vitro incubation with α-IFN was studied. The administration of a single dose of α-IFN increased NK cell cytotoxic activity significantly in the group of responders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…Previous studies have found an increased number of activated T cells and higher levels of serum neopterin in these patients, which suggest chronic stimulation of the immune system. Possible explanations include oxidative stress, frequent antigenic stimuli through blood transfusions, viral and bacterial infections and iron overload [8,23,24]. The potential involvement of drug therapy is also possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found an increased number of activated T cells and higher levels of serum neopterin in these patients, which suggest chronic stimulation of the immune system. Possible explanations include oxidative stress, frequent antigenic stimuli through blood transfusions, viral and bacterial infections and iron overload [8,23,24]. The potential involvement of drug therapy is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that thalassemic patients are affected by immune changes, including alterations in lymphocyte subsets, abnormal levels of cytokines and the presence of alloantibodies [21,22,23,24,25,26]. There is strong evidence of an association between endothelial cell activation and vascular complications in patients with β-thalassemia [6], whereas activation of the vascular endothelium is considered an important facet of inflammation, atherosclerosis [27,28,29], vasculitis and thrombosis [30,31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that thalassemia patients suffer from immunomodulation, including alterations in lymphocyte subsets, abnormal levels of cytokines, and the presence of alloantibodies [1,2,3,4,5,6,7]. It has been reported that thalassemia children have decreased levels of natural killer cells and increased activation of the expression of interleukin (IL) 2 receptor (CD25), HLA-DR, and CD45RO on lymphocytes [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thalassemia children have decreased levels of natural killer cells and increased activation of the expression of interleukin (IL) 2 receptor (CD25), HLA-DR, and CD45RO on lymphocytes [7,8,9]. Some of these immune abnormalities may make some thalassemics more susceptible to infections [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation